Analisis Perkembangan Pendidikan Berkualitas Sebagai Upaya Mewujudkan Tujuan Pembangunan Berkelanjutan (SDGs) - Oktavianatun, Anissa’; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Quality education plays a crucial role in achieving sustainable development goals (SDGs). This article presents an analysis of the development of quality education as an integral part of efforts to achieve SDGs. Through a descriptive-analytical approach, we explore various aspects related to the development of quality education and its impact on the achievement of SDGs. In this study, we analyze factors influencing the quality of education, including accessibility, curriculum relevance, teaching quality, and community empowerment in the education process. Additionally, we evaluate the extent to which quality education contributes to the achievement of SDGs, particularly in addressing social inequality, gender disparities, and economic empowerment. The results of the analysis indicate that quality education is a key pillar in sustainable development, as it plays a role in improving quality of life, reducing poverty, and creating inclusive and sustainable societies. Significant challenges still exist in achieving quality education for all, especially in rural and remote areas. Enhancing quality education as part of efforts to achieve SDGs involves increasing investment in educational infrastructure, developing curricula relevant to labor market needs, improving teacher training, and strengthening collaboration between governments, the private sector, and civil society in supporting inclusive and sustainable education.